Atypical presentation of anorexia nervosa pediatric patient: A multidisciplinary approach to diagnosis and management - Zainab Al Masseri; Afnan Aljawad; Zahrah Alkashi; Nadeer Albaik (Journal of Family Medicine and Primary Care)
This case report describes the complex presentation, diagnostic problems, and multidisciplinary therapy of a 13-year-old Syrian girl with an unusual form of anorexia nervosa (AN). The goal is to improve understanding of AN’s varied clinical spectrum while emphasizing the significance of a complete diagnostic approach and multidisciplinary therapy in juvenile cases. The patient reported considerable weight loss, amenorrhea, and physical indications of starvation over the previous two months. Notably, she did not exhibit the typical psychological symptoms linked with AN. Extensive examinations, including gastrointestinal, endocrinology, rheumatology, psychology, psychiatry, and neurology, were carried out to determine the underlying reason and develop a personalized care plan. The diagnostic process found unexpected traits that challenged established AN criteria. A multidisciplinary approach aided incorrect diagnosis and guided a treatment strategy that included nutritional rehabilitation, psychosocial support, and medical measures. The patient’s outcomes included weight gain, menstruation resumption, and hormonal and physical parameter normalization. This instance contributes to our growing understanding of AN as a group of illnesses with a variety of clinical manifestations. The patient’s atypical traits highlight the necessity for flexible diagnostic criteria and personalized, multidisciplinary care. The favorable outcomes demonstrate the possibility for positive outcomes with a complete strategy, paving the door for further investigation of diagnostic frameworks and treatment techniques in pediatric AN cases.